Charles Kittredge Crane papers - Crane, Charles Kittredge, 1881-1932.
Correspondence, reports, and printed matter relating to Crane's role in promoting international limitations on the manufacture and distribution of opium and other narcotics. Includes reports and plans submitted by Crane to the League of Nations and "C.K.C.-His Book," a compilation with a foreword by John Palmer Gavit documenting Crane's support for ratification of a Geneva convention on narcotic drugs. Correspondents include A.E. Blanco and John Palmer Gavit.
Reformer.
Collection material in English.
Keywords: Blanco, A. E. -- Correspondence; Gavit, John Palmer, -- 1868-1954.; Gavit, John Palmer, -- 1868-1954 -- Correspondence; League of Nations; Drug control -- International cooperation; Narcotics; Opium; Opium trade; Reformers